PEMBERDAYAAN IBU PKK MELALUI PENGELOLAAN INOVASI RASA KERIPIK SINGKONG DI DESA SEI BELURU - Sri Rahayu; Tarida Ilham Manurung; Novia Anjelia; Ayu Wulandari; Nuraini; Micael Olivan Siahaan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This empowerment program aims to describe the process of managing flavor innovations in cassava chips together with the PKK women in Sei Beluru Village. The background of this initiative lies in the potential of cassava as a local commodity, which is still largely limited to traditional processed products. Through this program, PKK women are encouraged to develop flavor innovations in cassava chips to enhance product appeal and expand market reach. The empowerment activities improve the women’s skills in cassava processing, create product variations, and strengthen family economic independence. Furthermore, the program fosters entrepreneurial spirit, strengthens solidarity among group members, and enhances the role of PKK women in village development. Therefore, empowerment that focuses on local product innovation proves to be an effective strategy in improving the rural community’s economy. Key words : Empowerment, PKK Women, Flavor innovation, Cassava chips, Rural economy.